SiAbasic: a comprehensive database for potent siRNA-6Ø sequences without off-target effects. (12th October 2018) - Park, Jongyeun; Ahn, Seung Hyun; Cho, Kwang Moon; Gu, Dowoon; Jang, Eun-Sook; Chi, Sung Wook
Abstract: Small interfering RNA (siRNA) is widely used to specifically silence target gene expression, but its microRNA (miRNA)-like function inevitably suppresses hundreds of off-targets. Recently, complete elimination of the off-target repression has been achieved by introducing an abasic nucleotide to the pivot (position 6; siRNA-6Ø), of which impaired base pairing destabilizes transitional nucleation (positions 2–6). However, siRNA-6Ø varied in its conservation of on-target activity (∼80–100%), demanding bioinformatics to discover the principles underlying its on-target efficiency. Analyses of miRNA–target interactions (Ago HITS-CLIP) showed that the stability of transitional nucleation correlated with the target affinity of RNA interference. Furthermore, interrogated analyses of siRNA screening efficiency, experimental data and broadly conserved miRNA sequences showed that the free energy of transitional nucleation (positions 2–5) in siRNA-6Ø required the range of stability for effective on-target activity (−6 ≤ ΔG[2:5] ≤ −3.5 kcal mol −1 ). Taking into consideration of these features together with locations, guanine-cytosine content (GC content), nucleotide stretches, single nucleotide polymorphisms and repetitive elements, we implemented a database named 'siAbasic' that provided the list of potent siRNA-6Ø sequences for most of human and mouse genes (≥ ∼95%), wherein we experimentally validated some of their therapeutic potency. siAbasic will aid to ensure potency of siRNA-6Ø sequences without concerning off-target effects for experimental and clinical purposes.